Growth of Epinephelus guaza under different culture conditions - Gracia López V.; Castelló-Orvay F. (Marine aquaculture finfish species diversification, 1995)
Since 1992 studies about the Ecology and the Culture of different species of Groupers has been conducted in our laboratory. The most important experiments about aquaculture has been done about Epinephelus guaza. In this paper, results of several trials about the effect of food, salinity, temperature and the artificial hiding space on the growth and feeding efficiency of this species are presented. A growth curve of juveniles of wild groupers from 7 to 458 g. raised in 500 liters tanks is shown.
Seminar of the CIHEAM Network on Technology of Aquaculture in the Mediterranean (TECAM), 1995/06/14-17, Nicosia (Cyprus)